Romantic myths and cyber dating violence victimization in Spanish adolescents: A moderated mediation model - María Jesús Cava Caballero; Isabel Castillo; Inés Tomás; Sofía Buelga (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2023)
Adolescents’ beliefs in romantic myths of love have been related to cyber dating violence victimization. However, these relationships could be mediated by adolescents’ tolerant attitudes toward dating abuse and be different for adolescent boys and girls. A better understanding of these relationships is important for developing more effective prevention programs. Thus, the current study aimed to examine the relationships between beliefs in romantic myths and cyber dating violence victimization in adolescents, analyzing the possible mediating role of tolerant attitudes toward abuse and the possible moderator role of gender. Participants were 467 Spanish adolescents who had a romantic relationship (54.4% girls; Mage = 15.09). Results showed positive significant direct and indirect relationships, through tolerant attitudes toward abuse, between beliefs in romantic myths and cyber dating violence victimization. Gender was not a moderator variable in the direct relationships, but its moderator role was supported in the indirect relationships. Stronger positive links between romantic myths and tolerant attitudes toward abuse, and between tolerant attitudes and cyber-control victimization, were found in adolescent girls. These findings highlight the need to consider tolerant attitudes toward abuse in intervention programs designed to prevent cyber dating violence victimization in adolescents and continue to analyze gender differences in variables related to cyber dating violence victimization.